KARAKTERISTIK MORFOLOGI DAN KIMIAWI BEBERAPA VARIETAS UBI KAYU MANIS ASAL KECAMATAN PALAS, KABUPATEN LAMPUNG SELATAN BERDASARKAN UMUR PANEN YANG BERBEDA - Siti Nurdjanah; Susilawati Susilawati; Udin Hasanudin; Ayu Anitasari (JURNAL AGROTEKNOLOGI, 2020)
Most of cassava grown in Palas, South Lampung District is sweet type cassava (Manihot esculenta Crantz) utilized as raw materials for cassava-based snack production. However, their characteristic had never been reported. The aims of the research were to determine the effect of varieties, harvesting age, and interaction between varieties and the harvesting age on morphology and chemical characteristics of sweet type cassava planted in Palas District, South Lampung. The experiment was factorial and arranged in a Complete Randomized Block Design (CRBD) with two factors and four replications. The first factor was cassava variety, i.e., manalagi (V1), mentega (V2), and krembi (V3). The second factor was the harvest age (U) i.e., 7-8 months (U1) and 8-9 months (U2). Morphology data were reported descriptively, while data for other characteristics were tested for homogeneity and additivity using Barlett and Tuckey test, then subjected to ANOVA, and further tested using Duncan test at the level of 5%. The results showed that the variety and harvest age significantly affected of water content, starch yield, starch content, amylose, and amylopectin. There was a significant interaction between varieties and age of harvest on moisture content, starch yield, and starch content, but there was no significant interaction effect on amylose and amylopectin. The highest value of moisture content was found in manalagi aged at 7-8 months (67.28% wb), the highest value of starch yield was found in manalagi age at 8-9 months of (16.34%), the highest value of starch content was found in mentega aged at 8-9 of months (17.52 % wb), the highest value of amylose was found in mentega aged at 8-9 of month (10.35% db), the highest value of amylopectin was found in krembi aged at 7-8 of month (92.78% db). Overall, krembi, manalagi, and mentega can be categorized as low-amylose cassava which has potential to be developed as raw material for crispy cassava-based snack. Keywords: harvesting age, krembi, low-amylose cassava, manalagi, mentega